The Effect Of Stress And Breast Care During The Covid-19 Pandemic On The Currency Of Post Partum Mom's Breast Milk (ASI) In Indramayu District - Nurohmat Nurohmat; Indra Ruswadi; Nengsih Yulianingsih (Universitas Pendidikan Indonesia, 2021)
One of the psychological disorders that can occur in postpartum mothers is that mothers experience post-delivery stress, especially for primiparous mothers in other words, in normal situations postpartum mothers face various problems, plus during the COVID-19 pandemic, of course, it can cause stress so that it is feared to have an impact on the baby. because the milk is not smooth. The purpose of this study was to analyze the effect of stress and breast care during the COVID-19 pandemic on the smoothness of postpartum mother's milk in Indramayu Regency with the associative method using descriptive and inferential statistical analysis approaches. Based on the results of research conducted from April to July 2021 in Indramayu Regency, the following conclusions can be drawn: 36.7% postpartum mothers during the covid 19 pandemic experienced moderate stress, 55.1% postpartum mothers during the covid 19 pandemic included the category not good. and 57.1% of postpartum mothers during the covid 19 pandemic in Indramayu Regency, their breast milk is in the substandard category.